Cyclostratigraphy of an orbitally-driven Tithonian–Valanginian carbonate ramp succession, Southern Mendoza, Argentina: Implications for the Jurassic–Cretaceous boundary in the Neuquén Basin - Kietzmann, Diego Alejandro (2015)
Detailed sedimentological, sequence stratigraphical and cyclostratigraphical analyses have been made from four lower Tithonian–lower Valanginian sections of the Vaca Muerta Formation, exposed in the southern Mendoza area of the Neuquén Basin, Argentina. The Vaca Muerta Formation is characterized by decimetre-scale rhythmic alternations of marls, shales and limestones, and consists of five facies associations, which reflect different paleoenvironmental conditions: basin to restricted outer ramp, outer ramp, and middle ramp. Vertical organization within the Vaca Muerta Formation shows a well-ordered hierarchy of cycles, where elementary cycles, bundles and superbundles with frequencies within the Milankovitch band have been recognized. According to biostratigraphic data, elementary cycles have a periodicity of ~ 20 ky, which correlates with the precession cycle of Earth's axis. Spectral analysis based on series of cycle thickness allows us to identify frequencies of about 400 ky and 90–120 ky, which we interpret as the modulation of the precessional cycle by the Earth's orbital eccentricity. Cycles are probably driven by variations in carbonate exportation, as fluctuations in shallow-water carbonate production involve modifications in carbonate basinward exportation. Cyclostratigraphic data allowed us to build a floating orbital scale for the Tithonian–lower Valanginian interval in the Neuquén Basin. Correlation between studied sections allowed us to recognize a discontinuity between the Substeueroceras koeneni and Argentiniceras noduliferum ammonite zones in the Malargüe Anticline area. Orbital calibration of these sections is consistent with Riccardi's biostratigraphic scheme, wich place the Jurassic-Cretaceous boundary within the Substeueroceras koeneni ammonite Zone. On the other hand, the base of the Vaca Muerta Formation (Virgatosphinctes mendozanus ammonite Zone) would be probably placed in the base of the middle Tithonian rather than the lower Tithonian, which is also consistent with our preliminary palaeomagnetic data.